Formulasi dan Evaluasi Sediaan Krim Ekstrak Daun Sirih dengan Variasi Konsentrasi Etanol 96% Sebagai Antiseptik - Aini, Hilfa Qurrotul; Tiadeka, Pemta; Naimah, Janatun (PHARMADEMICA : Jurnal Kefarmasian dan Gizi, 2024)
The betel leaf plant (Piperis betle Linn) is a plant that is very easy to find in the surrounding environment. One of the benefits of the betel leaf plant is for treatment as an antiseptic because it contains flavonoid compounds. In order to make it easier for users to use betel leaves (Piperis betle Linn) as an antiseptic, the leaves are extracted with 96% ethanol and then formulated in cream form. This research aims to determine the results of concentration variations on the antiseptic activity of 96% ethanol extract cream from betel leaves on wound healing. Betel leaves (Piperis betle Linn) were extracted using the maceration method using 96% ethanol. Then the extract is made into a cream mass with varying concentrations of the active substance of 4%, 8% and 12%. The results of research on the formulation and evaluation of betel leaf extract cream can be concluded that betel leaves can be formulated as an antiseptic. The results of the physical evaluation show that the betel leaf extract cream has the best preparation in formula II with a concentration of 4% because the cream is included in the test range).